2014
DOI: 10.1007/s11103-014-0264-z
|View full text |Cite
|
Sign up to set email alerts
|

GsSKP21, a Glycine soja S-phase kinase-associated protein, mediates the regulation of plant alkaline tolerance and ABA sensitivity

Abstract: Plant SKP1-like family proteins, components of the SCF complex E3 ligases, are involved in the regulation of plant development and stress responses. Little is known about the precise function of SKP genes in plant responses to environmental stresses. GsSKP21 was initially identified as a potential stress-responsive gene based on the transcriptome sequencing of Glycine soja. In this study, we found that GsSKP21 protein contains highly conserved SKP domains in its N terminus and an extra unidentified domain in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The area of saline–alkali soils covering western Songnen Plain has been expanding. Much of this soil contains alkaline salts like Na 2 CO 3 and NaHCO 3 , severely threatening crop growth and productivity (Liu et al ). With the development of functional genomics and bioengineering technologies, researchers have attempted to exploit the alkalized soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The area of saline–alkali soils covering western Songnen Plain has been expanding. Much of this soil contains alkaline salts like Na 2 CO 3 and NaHCO 3 , severely threatening crop growth and productivity (Liu et al ). With the development of functional genomics and bioengineering technologies, researchers have attempted to exploit the alkalized soil.…”
Section: Discussionmentioning
confidence: 99%
“…To overexpress GsSLAH3 in Arabidopsis, the coding region of GsSLAH3 was cloned (forward: 5′‐AGGCCCGGGATGGAAAACAACCTTAACCGT‐3′ and reverse: 5′‐TCGTCTAGATCATGGCTCCCAAGTCTTAAATGG‐3′) and inserted (SmaI and XbaI) into pCAMBIA2300 (Liu et al ). The recombinant vector was transformed into Agrobacterium tumefaciens strain LBA4404.…”
Section: Methodsmentioning
confidence: 99%
“…Another study also demonstrated that transcript abundance of GsSKP21 was induced under the treatment of alkali and salt stresses in Glycine soja . Overexpression of GsSKP21 in Arabidopsis results in decreased ABA sensitivity and promoted seed germination [ 49 ]. Moreover, the accumulation of glutamate decarboxylase (GAD) and alcohol dehydrogenase (ADH) are also promoted in both sd1 mutant and BRZ-treated Nip ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…ASK1 has further been found to be involved in meiotic events and flower development ( Yang et al , 1999 , 2006 ; Wang and Yang, 2006 ; Lu et al , 2016 ). Recent studies have determined the roles of SKP proteins in abiotic stress tolerance in several plant species, including Paeonia suffruticosa , Triticum aestivum , and Glycine soja ( Li et al , 2012 ; Liu et al , 2015 ; Hao et al , 2017 ). Expression analysis of various ASK proteins in Arabidopsis has also suggested their participation in the seed germination processes ( Marrocco et al , 2003 , Zhao et al , 2003 ; Takahashi et al , 2004 ; Dezfulian et al , 2012 ; Kuroda et al , 2012 ).…”
Section: Introductionmentioning
confidence: 99%